(untitled) (Economics and region, 2024)
A study of the theoretical aspects of the role of economic (macroeconomic) policy strategizing in the system of state regulation was carried out. It was noted that the issue of outlining one’s own unique path from the perspective (vision) of socio-economic development is still relevant, that is, what the state should achieve in the future, taking into account historical circumstances and institutional changes, in order to improve human well-being. It is recognized that it is important to take into account the influence of the constantly changing external environment, and these changes are characterized by the concept of the VUCA world (the world is unstable and unpredictable), which is replaced by the BANI world (the world is fragile and incomprehensible). It is emphasized that an important condition for achieving a high level of economic policy effectiveness is to take into account the main ideas and concepts of representatives of various economic schools, which are the property of world economic science and on the basis of which macroeconomic policy is implemented in many countries of the world, primarily in countries with developed economies. The factors that have a decisive influence on the further socio-economic development of the state are revealed. It is noted that when determining the content of economic policy, scientists ignore the fact that it is impossible to achieve certain economic goals only with the help of economic policy means. It has been clarified that the mutual influence, interaction and relationship between all types of state policy will become more and more important in the future. Furthermore, it is noted that it is necessary to take into account the factor of the existence of a close relationship between economic policy and other types of policy (social, humanitarian, information and institutional, state policy in the field of marketing and branding, etc.), and it is clarified that to ensure the high efficiency of state regulation in particular, the issue of their mutual agreement and coordination becomes more relevant. It was emphasized that the construction of a socially oriented, innovative market economy, primarily an economy (noo-economy) based on man and "everything for man," is of great importance for our state.